(3NHQ GdYGde heG LQi dg eY GdEeGe Ydj Hf CHj WGdH Ydjg GdSdGes - (3eLghds ((3Ydj GdMSjfjs)
(3ChdgG (B:s
(3Qhj Yf Ydj Hf CHj WGdH Ydjg GdSdGe bGd cfJ LGdSG PGJ jhe aj LGeY GdchaI hEPG HUjMI YXjeI YGdjI bO GQJaYJ abGd GdEeGe Ydjg GdSdGe dbfHQ jG bfHQ GeV hGFJfj ef gPg GdUjMI HGdNHQ (B...s
(3BNQgG (B:s
.. (3aQaY GdEeGe QCSg Edi GdSeGA bGd Edgj CfJ GdYGde HeG bGd YHOc GdYGde aSLO GdYGde SLOI aCWGd ajgG GdSLhO aMQchg aEPG gh bO eGJ aZSdg CejSQ GdeDefjf Ydjg GdSdGe hcafg hUdi Ydjg(B,s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3ddeTgO GdQVhjs
Keywords: (3GdJGQjNs